Educating and engaging higher learning students with interactive games of information management education (i-GIME) v.2 - Kamarudin, Nurfaizah; Halamy, Suhaida; Mohsin, Mohsinin (Academica Press Solutions, 2023)
Game-based learning has grown in popularity since used during Covid-19. Many educators worldwide use game-based learning as an exciting and interactive tool. i-GIME v.2 has been enhanced with additional modules and menus to make learning and teaching more engaging and students more interested and motivated. The purpose of i-GIME v.2 is to help information management students improve their information literacy and cataloguing skills. i-GIME v.2 designed the course content with gaming components that revolutionized the teaching and learning technique using a few website applications. The importance of i-GIME v.2 can stimulate learning motivation and student activity to be engaged in learning. In addition, the application of game-based learning can also improve student learning outcomes and creativity. An online survey was undertaken to assess students' perceptions of i-GIME v.2. The survey included 46 students from a public higher education institution. According to the frequency analysis, the game-based learning technique boosted students' self-efficacy in information literacy and cataloguing skills. As a result, the authors conclude that game-based learning provides better findings in student learning than traditional classroom teaching.